THE ROLE OF INNOVATIVE BEHAVIOR TOWARDS THE PERFORMANCE OF HUMAN RESOURCE BASED ON ORGANIZATIONAL LEARNING AND ISLAMIC LEADERSHIP - Lily Prabawati; Mutamimah Mutamimah (UNISSULA, 2017)
This study examines the Role of Innovative Behavior towards the human resource based on Organizational Learning and Islamic Leadership which aims to describe and analyze the effect of organizational learning on innovative behavior, the effects of organizational learning on HR performance, the effects of Islamic leadership on innovative behavior, the effects of Islamic leadership on HR performance,innovative behavior towards HR performance. Respondents of this study were all human resources working in Secretariat of Semarang district accounted for 115 people. The sampling technique used in this study is census so that this research used 115 respondents. Data analysis technique used is regression analysis of path analysis model (path analysis). The results showed that organizational learningvariable has positive and significant effects on innovative behavior. Organizational learning has a positive and significant effect on HR performance. Islamic leadership has a positive and significant effect on innovative behavior. Islamic leadership has a positive and significant effect on HR performance. Innovative behavior positively and positively affects HR performance. Increased innovative behavior leads to a significant increase in HR performance.Keywords: organizational learning, Islamic leadership, innovative behavior, HR performance.